Software Design for Inventory Management Improvement in a Peruvian National University - Linett Velasquez; Santiago Rubiños; Junior Grados; Juan Grados; Claudia Marrujo (Journal of Applied Engineering and Technological Science)
The purpose of this study was to design a software to optimize inventory management in the Office of Information Technology and Communications (OTIC) of the Faculty of Industrial Engineering and Systems of the Universidad Nacional del Callao, Peru. The research arose due to the lack of an efficient system that minimizes asset losses and reduces operational errors in the university context, where resource constraints demand sustainable and adaptable solutions. To address this problem, an agile methodological approach was used, implementing the Scrum methodology in the software design, as well as an architecture based on MVC (Model-View-Controller) with technologies such as MySQL, PHP and CodeIgniter. The evaluation of the system included usability surveys to users and an expert judgment, focused on three dimensions: Reliability, Usability and Design. The results of the study showed a high acceptance of the system in terms of ease of use and user satisfaction, highlighting the effectiveness of the modular design for future extensibility and performance improvements. This study provides theoretical value by highlighting the application of agile methodologies in educational environments and highlights the importance of a scalable design to improve inventory management in academic institutions. In practical terms, the implementation of this software offers an adaptable and scalable solution, with potential for replication in other universities, optimizing resource management and strengthening operational efficiency in the educational sector. The main contribution of the study lies in the combination of a flexible and low-cost design, aimed at meeting the specific needs of inventory management in educational environments with budgetary constraints.